Genital examinations in cases of suspected ‘female genital mutilation’ in Sweden 1982–2022: lawful decisions resulting in structural injustice - Sara Johnsdotter; Lotta Wendel; Klara Grönvall; Birgitta Essén (Humanities & Social Sciences Communications)
Abstract This paper critically examines the disproportionate impact of Sweden’s legal and policy measures aimed at detecting and prosecuting ‘female genital mutilation’ (FGM) within immigrant communities. Despite three criminal court cases related to FGM performed in African countries, forced genital examinations—central to many investigations—have not resulted in any prosecutions. This raises significant concerns about the effectiveness and proportionality of current practices. Drawing on an archive of police case files and interviews with professionals involved in FGM investigations, we explore how legal frameworks, while intended to protect children, apparently indicate a pattern of over-policing and structural injustice. Our analysis highlights the disconnect between policies rooted in suspicion and control and the cultural shifts occurring within affected communities, where attitudes toward the circumcision of girls have evolved due to migration. We argue that Sweden’s reliance on invasive measures risks exacerbating the marginalisation of immigrant groups and underscores the need for more nuanced, trust-building approaches. The findings call for a re-evaluation of current strategies to ensure that interventions are proportionate and sensitive to evolving cultural contexts, while still protecting the rights and well-being of children.